2022
DOI: 10.1177/21925682221098667
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Lumbar Curve Flexibility and Apical Vertebral Rotation for the Prediction of Spontaneous Lumbar Curve Correction in Selective Thoracic Fusion for Lenke Type 1 and 2 C Curves: Retrospective Cohort Study with a Mean Follow-Up of More than 10 years

Abstract: Study Design Retrospective analysis of a prospectively collected data. Objective Lumbar flexibility(LF) is generally defined with preoperative side bending films;it is not clear what percentage of LF predicts the spontaneous lumbar curve correction (SLCC) at long term follow up. Aim of this study was to find out cut-off value of preoperative LF,apical vertebra rotation(AVR) and apical vertebral translation(AVT);which may predict more than 50%SLCC. Methods Patients with Lenke 1C&2C curves,treated with poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Assessment of the axial plane of AIS, with rotation of the apical vertebra as its most important parameter, has attracted increasing interest in recent years. 1,2,[5][6][7]9,13 The degree of vertebral rotation can be useful for monitoring the progression of scoliosis and assessing treatment results. 5,[14][15][16] Accurate assessment of vertebral rotation allows prediction of curve progression, the degree of correction, and possible decompensation of the coronal balance of the spine in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Assessment of the axial plane of AIS, with rotation of the apical vertebra as its most important parameter, has attracted increasing interest in recent years. 1,2,[5][6][7]9,13 The degree of vertebral rotation can be useful for monitoring the progression of scoliosis and assessing treatment results. 5,[14][15][16] Accurate assessment of vertebral rotation allows prediction of curve progression, the degree of correction, and possible decompensation of the coronal balance of the spine in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[5][6][7]9,13 The degree of vertebral rotation can be useful for monitoring the progression of scoliosis and assessing treatment results. 5,[14][15][16] Accurate assessment of vertebral rotation allows prediction of curve progression, the degree of correction, and possible decompensation of the coronal balance of the spine in the postoperative period. 5,6 Behensky et al, 6 in a retrospective review of Lenke type 3C AIS, concluded that rigid rotational deformity of the lumbar curve (vertebral rotation correction of less than 40% in the slopes) results in coronal imbalance in the postoperative follow-up in selective thoracic fusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Однако авторами не было выявлено статистических различий между результатами нового метода и ранее разработанными [7]. Также важное значение точность оценки ротации апикальных позвонков имеет при анализе различных типов деформации идиопатического сколиоза и трехмерного анализа полученной послеоперационной коррекции деформации позвоночника [14,15].…”
Section: результаты исследования и их обсуждениеunclassified